Stromal Vascular Fraction-based patches generated under perfusion culture enhance cardiac function in rats with chronic myocardial infarction. (10th June 2022) - Gili Sole, L; Reid, G; Perera, M; Acar, E; Weber, L; Szabo, L P; Pilz, P; Eckstein, F; Santer, D; Friske, J; Podesser, B; Helbich, T H; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Foundation The development of novel adjuvant angiogenic therapies to restore the low-perfused microvascular network upon myocardial infarction (MI) is crucial to avoid a possible end-stage heart failure. Of the current adult cell-based therapies, human adipose tissue-derived stromal vascular fraction cell (SVF) has vast reparative potential, principally due to: 1) its heterogeneous composition rich in mesenchymal stem cells (MSC), endothelial cells (EC), pericytes and hematopoietic cells, among others. In vitro engineering of SVF-based patches under unidirectional flow, applied by the help of a perfusion-based bioreactor, was found to increase certain cellular SVF subgroups such as pericytes, compared to static culture. In this study, we aimed at studying the potential of SVF-based engineered tissues in a model of chronic MI in nude rats. Human SVF cells were isolated upon liposuction and cultured on 3D collagen sponges (8 mm diameter, 3 mm thickness) either under constant unidirectional perfusion or in static condition for 5 days. Patches were characterized in terms of cellular composition prior to implantation. MI was induced by permanent ligation of the left anterior descending (LAD) coronary artery in male nude rats. Cardiac MRI was performed 4 weeks after MI; prior to the suture of patches and before sacrifice (4 weeks after implantation). Left ventricular ejection fraction (EF) was the surrogate marker and primary end point for cardiac pump function. Controls included untreated MI animals. Following perfusion culture, SVF cells were composed with a statistically superior percentage of pericytes, identified as CD45- CD34- CD146+ compared to static culture (28.06±10.03 and 3.37±2.50, respectively, p<0.0007). The presence of other cell subpopulations was similar in the patches generated in perfusion or static culture. While the percentage of EF at the time of sacrifice resulted to be not statistically different between static and perfusion-based patches, statically generated constructs showed a general trend of decrease in the % EF before and after treatment (rat 1: 61.96 vs 52.90; rat 2: 55.39 vs 53.00; rat 3: 52.34 vs 50.62, respectively). Perfusion-cultured patches, instead, rather improved the cardiac function, measured as % EF (rat 1: 51.82 vs 58.72; rat 2: 51.66 vs 60.45; rat 3: 53.50 vs 52. 36, respectively for 4 weeks following MI and 4 weeks following treatment). When comparing the ratio of the % EF 8 weeks and 4 weeks between static or perfusion-based patches and the untreated controls, rats treated with patches generated under perfusion resulted to show higher levels of % EF, with an almost statistically difference (p=0.0556), compared to the control group. The observed results showed the great potential of human SVF-based patches in the improvement of the heart pump function.